More than money: exploring the role of investment advisors for sustainable investing. Issue 1 (8th June 2015) - Paetzold, Falko; Busch, Timo; Chesney, Marc
Abstract : Purpose: – Investment advisors play a significant role in financial markets, yet the determinants of their behavior have not been explored in detail. The purpose of this paper is to explore the determinants of how actively advisors communicate about sustainable investing with their clients, and differences in the preferences of advisors compared to investors. Design/methodology/approach: – Based on a survey with 296 retail and private banking investment advisors, this study employs an ordinary least squares regression model to explore the determinants of advisors activity in communicating about sustainable investing (SI) with their clients, differences in the aspects that matter to advisors and investors, and the role of the complexity of sustainability. Findings: – Advisors activity in communicating about SI relates to their expectation of SI regarding financial return, real-world impact, and the fuzziness and trustworthiness of SI. Advisors appear not to be influenced by expected risk and their personal values, which runs against prior research findings and the interest of investors. Research limitations/implications: – Future research should assess cultural differences and explore asymmetries between advisors and investors in regard to the role of volatility, values, impact measurement, and complexity. Practical implications: – Investment advisors underweighting aspects related to risk and self-transcendent values relative to their clients might limit the suitability of clients ' portfolios, skew capital allocation, and depress the role of SI in financial markets. Generalized to salespeople this behavior might depress the market success of products related to sustainability at large. Social implications: – The findings and their generalization indicate that salespeople might systematically deviate from their clients' interests in regard to social responsibility. Advisors and salespeople in their mediating role might be an important barrier to sustainable development. Originality/value: – This is the first quantitative study that explores the decision-making by investment advisors in the context of SI, and as such answers to specific calls in literature to explore the micro-foundations of decision making in regard to SI and social responsibility, and on the relationship between private investors and investment advisors. This study is based on unique and original empirical data on advisors that work with retail and wealthy private investors.